Open data concept, its application and experiences - Terzić, Rajko M.; Majstorović, Milosav N. (Vojnotehnički glasnik / Military Technical Courier, 2018)
Creating a richer, more equitable and just society requires that governments work in a more transparent and responsible way - to maintain regular and meaningful communication with citizens. Open data is the means to achieve this goal. Open data is digital data available to the public. It has such technical and legal characteristics that anyone, at any time and everywhere can use, re-use and redistribute it. The focus in this paper is data that is easily accessed and used and distributed for free. It is structured for usability and computer analysis. Such data is called publicly available or open data. The paper deals with the basic concepts of Open data, where it is most used, the most important experiences and benefits in its use, how it impacts human lives, which foregoing preconditions have to be met in order to significantly increase the effects of open data, how influence is created with it and the challenges that arise in its use.